2018
DOI: 10.1080/15548627.2018.1531197
|View full text |Cite
|
Sign up to set email alerts
|

MITF-MIR211 axis is a novel autophagy amplifier system during cellular stress

Abstract: Macroautophagy (autophagy) is an evolutionarily conserved recycling and stress response mechanism. Active at basal levels in eukaryotes, autophagy is upregulated under stress providing cells with building blocks such as amino acids. A lysosome-integrated sensor system composed of RRAG GTPases and MTOR complex 1 (MTORC1) regulates lysosome biogenesis and autophagy in response to amino acid availability. Stress-mediated inhibition of MTORC1 results in the dephosphorylation and nuclear translocation of the TFE/ M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 51 publications
(65 reference statements)
0
35
0
1
Order By: Relevance
“…This complex network of phosphorylation events is primarily devoted to regulating TFEB subcellular localization in response to nutrient availability: under nutrientrich conditions, phosphorylation drives TFEB nuclear export and cytoplasmic retention; under glucose limitation, activation of mTORC2 leads to AKT-mediated inhibition of GSK3 and reduced nuclear export (Li et al 2018), while amino acid limitation inactivates mTORC1 and releases TFEB from its cytoplasmic anchor (Roczniak-Ferguson et al 2012). Notably it has recently been shown that the critical mTORC2 subunit RICTOR is targeted by miR-211 (Ozturk et al 2018), a microRNA whose expression is activated by MITF (Miller et al 2004;Boyle et al 2011;Margue et al 2013), and likely also by TFEB and TFE3. Since inactivation of mTORC2 signaling by miR-211 leads to inactivation of mTORC1, nutrient limitation that triggers nuclear accumulation of MiT family members and increased miR-211 expression activates a feedforward loop that amplifies MiT family nuclear accumulation and their downstream transcription program (Ozturk et al 2018).…”
Section: Tfeb Tfe3 and Nonmelanocyte Isoforms Of Mitfmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex network of phosphorylation events is primarily devoted to regulating TFEB subcellular localization in response to nutrient availability: under nutrientrich conditions, phosphorylation drives TFEB nuclear export and cytoplasmic retention; under glucose limitation, activation of mTORC2 leads to AKT-mediated inhibition of GSK3 and reduced nuclear export (Li et al 2018), while amino acid limitation inactivates mTORC1 and releases TFEB from its cytoplasmic anchor (Roczniak-Ferguson et al 2012). Notably it has recently been shown that the critical mTORC2 subunit RICTOR is targeted by miR-211 (Ozturk et al 2018), a microRNA whose expression is activated by MITF (Miller et al 2004;Boyle et al 2011;Margue et al 2013), and likely also by TFEB and TFE3. Since inactivation of mTORC2 signaling by miR-211 leads to inactivation of mTORC1, nutrient limitation that triggers nuclear accumulation of MiT family members and increased miR-211 expression activates a feedforward loop that amplifies MiT family nuclear accumulation and their downstream transcription program (Ozturk et al 2018).…”
Section: Tfeb Tfe3 and Nonmelanocyte Isoforms Of Mitfmentioning
confidence: 99%
“…Notably it has recently been shown that the critical mTORC2 subunit RICTOR is targeted by miR-211 (Ozturk et al 2018), a microRNA whose expression is activated by MITF (Miller et al 2004;Boyle et al 2011;Margue et al 2013), and likely also by TFEB and TFE3. Since inactivation of mTORC2 signaling by miR-211 leads to inactivation of mTORC1, nutrient limitation that triggers nuclear accumulation of MiT family members and increased miR-211 expression activates a feedforward loop that amplifies MiT family nuclear accumulation and their downstream transcription program (Ozturk et al 2018). In addition, AKT-mediated phosphorylation of S467 decreases TFEB protein stability such that AKT inhibition can lead to increased nuclear accumulation of TFEB (Palmieri et al 2017).…”
Section: Tfeb Tfe3 and Nonmelanocyte Isoforms Of Mitfmentioning
confidence: 99%
“…Under stress conditions, including starvation, miR‐211 directly targets RICTOR, a component of mTORC2, which, in turn, inhibits the mTORC1 pathway and stimulates translocation of the transcription factor MITF to the nucleus. This MITF–miR‐211 axis completes an autophagy amplification loop system that controls autophagic activity in cells . miR‐155 inhibits autophagy by suppressing several Atg genes, including ULK1, FOXO3, Atg3, Atg5, Atg14, and LC3, at both the mRNA and protein levels .…”
Section: Molecular Regulation Of Autophagy Machinerymentioning
confidence: 99%
“…However, it should be noted that the effects of ESC‐sEVs on mTORC1 inhibition and H‐NSCs senescence were not entirely abolished by miRNAs blocked in ESC‐sEVs, suggesting the presence of additional miRNAs may be involved in these processes. As list in Table S3 (Supporting Information) of microarray, miRNAs like miR‐211‐3p, [ 49 ] miR‐214‐3p, [ 50 ] miR‐184, [ 51 ] and miR‐99a‐5p, [ 52 ] which can inhibit mTORC1 activation, were also contained in ESC‐sEVs though in low level and may function to rejuvenate H‐NSCs senescence. In addition, as we previously demonstrated ESC‐sEVs can transfer highly enriched miR‐200a to ameliorate endothelial senescence by upregulation of Nrf2, [ 24 ] while whether miR‐200a in ESC‐sEVs can function in senescent H‐NSCs still needs further exploration.…”
Section: Discussionmentioning
confidence: 99%